PENERAPAN AKUNTANSI SYARIAH DALAM ASURANSI SYARIAH DI INDONESIA - Komarudin, Komarudin; Nur Hotami; Muhammad Nabil Zulkarnain; Hj. Mukhlishotul Jannah (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
With the rapid growth of the global economy, there are many financial companies in Indonesia, both bank-based and non-bank-based. With this development, the Muslim community began to question the existence and operation of financial institutions. Shariah-based financial institutions were established because the Muslim community was skeptical of the operations of conventional financial institutions. However, as Islamic financial institutions developed rapidly, the community began to treat their accounting like conventional financial institutions, which prompted the establishment of an Islamic accounting system. The author uses a research study method that collects information from books and scientific journals to discuss the Islamic accounting system in Islamic insurance in this context. The results of the discussion show that Islamic accounting is a process that refers to Islamic law to record, classify, process, and report the finances of a company during a certain period of time. The principle of fairness is used in the accounting system of sharia-based insurance. Islamic accounting focuses on the principles of sharia, distinguishing it from general accounting. In Islamic insurance, premiums received before the transaction date are recognized in the financial statements of the following period. The author concludes from these findings that Islamic insurance has used accounting in accordance with Islamic law, namely sharia accounting. In preparing financial statements for Islamic institutions such as Islamic insurance, Islamic accounting is very important. We can make better reports by better understanding the concept of Islamic accounting.